(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This study aims to identify the importance and advantages of Smartphone applications and assess their impact on the scientific research process at Tishreen University . Specifically, it examines the awareness and skills of students in using these application to enhance the benefits , efficiency , and effectiveness of scientific research. The research employs a field method, utilizing a questionnaire distributed to 50 graduate students from the faculty of Civil Engineering at Tishreen University. The finding reveal varying levels of Smartphone usage among the participants : 10% use their phones for 1-2 hours daily,54% for 3-6 hours, 28% for 7-9 hours , and 8% for more than 9 hours . significant relationships were identified between the perception of the need for Smartphone applications and the achievement of research benefits, as well as between perception, efficiency , and effectiveness. Additionally, a significant relationships was observed between usage skills and the combined efficiency and effectiveness of research. The study recommend developing training programs for students, particularly graduate students, to enhance their skills in using Smartphone applications for scientific research. it also suggests encouraging universities and research and improving internet connectivity and access points within universities, especially for faculty members and graduate students.